ANALISIS PENGARUH INDEPENDENSI, OBYEKTIFITAS, INTEGRITAS,KOMPETENSI, PENGALAMAN KERJA DAN SKEPTISISME PROFESIONAL TERHADAP KUALITAS HASIL PEMERIKSAAN DI LINGKUNGAN INSPEKTORAT PROVINSI JAMBI - Mufidah Mufidah (Universitas Batanghari Jambi, 2015)
The title of this research is Analyze the Effect of Independence, Objectivity, Integrity, Competence, Work Experience and Professional Skepticism Towards the Quality of Examination Results in Jambi Province Environmental Inspectorate. This study aimed to analyze the effect of Independence, Objectivity, Integrity, Competence, Work Experience and Professional Skepticism towards the quality of examination results in Jambi Province Environmental Inspectorate simultaneously or partially. This research is a descriptive survey of the Office of the Jambi Provincial Inspectorate checks throughout the county and municipalities on SKPD in Jambi. Data is collected by field and library research . The time horizon used is cross section. The number of respondents that auditors and supervisors as much as 59 people. The data analysis to test the hypothesis is using multiple regression analysis by SPSS program .The result of this research shows that the Independence, Objectivity, Integrity, Competence, Work Experience and Professional Skepticism have significant effect towards the qua lity of examination results. Objectivity, Integrity, Competence, Work Experience and Professional Skepticism partially significant effect on the quality of inspec tion results, but independence only partially not significant effect.Keywords: Independence, skepticism and the quality